The Effect of Giving Cookies Based Local Food on The Body Weight of Stunting Toddlers With Underweight - Endah Sulistiowati; AASP Chandradewi; Reni Sofiyatin; Made Darawati (Jurnal Kesehatan Prima, 2023)
Based on Indonesian nutritional status survey  report in 2021 the incidence of underweight (weight according to age) nationally in 2021 is 17.0%, an increase of 8% from 2019, for the West Nusa Tenggara provincial level at 23.0%, it ranks 26th out of 34 provinces, and at the regency level in 2021, Dompu regency is 10.9% while at the Puskesmas level, East Dompu health center contributes 19.11%. The purpose of study is to analyze effect of giving cookies-based local food on the body weight of stunting toddlers with underweight. This research was conducted in O'O Village, Dompu regency, with data collection and intervention carried out from 4 May to 8 May, 2022. This type of research is a Quasi-Experimental study with one group pre-and post-test design. The sample that meets the inclusion requirements is as many as 21 people. Four stars cookies are given for five days, one pack per day containing six pieces. The analysis used the paired T-test. The results showed that there was an average toddler weight gain of 0.45 kg during the intervention, and statistically, with different trials, there was a significant difference (p<0.05). Although there are significant results from this study, this study has a weakness in the number of intervention days, which is too short, so that to get a body weight that is by the recommended dietary allowances (RDA) has not been achieved, and it is necessary to increase the number of administrations to meet the requirements for giving supplemental feeding program.